PENGARUH E SERVICE QUALITY DAN BRAND AWARENESS TERHADAP LOYALITAS KONSUMEN PT BRI UNIT KAWUNGANTEN - Nuni Wulansari; Fajar Nur Wibowo; Lia Ernawati; Meylani Dwi Ningrum (Pusat Riset dan Inovasi Nasional, 2021)
This study aims to analyze the effect of service quality and brand awareness on consumer loyalty at PT BRI Kawunganten Unit. The object of this research is Bank BRI Kawunganten Branch, while the subject is BRI Kawunganten Bank customers. This research uses sampling with purposive sampling technique. The number of samples in this study were 97 respondents. Data were obtained through questionnaires which were distributed directly to BRI Kawunganten Bank customers. The data analysis technique uses SPSS version 22. Based on the results of the analysis performed, it shows that E-Service Quality has a positive effect on Consumer Loyalty and Brand Awareness has a positive effect on Consumer Loyalty.